Sistem Pendukung Keputusan Uang Kuliah Tunggal dengan Metode Activity Based Costing - Winarno Winarno; Eko Nugroho; Indriana Hidayah (Jurnal Akuntansi dan Bisnis, 2014)
Higher education is one of education institution with tight competition. University have to increase their quality to captivate the public. In addition to consideration of the quality of higher education, the cost of education is also a consideration for choosing a university. In 2012, Indonesia has 33 universities in a form of Badan Layanan Umum (BLU). According to PMK no 76 2008, BLU must have a Cost Accounting System which generates unit cost. It’s used by university to define their tuition fee. In 2013 many of BLU universities don’t have a cost structure analysis. The research goal is designing, creating application that can define unit cost in a BLU university with Activity Based Costing (ABC) method. The research use PHP as programming language and MySQL as database engine. The result of this research is design the system, prototype and testing the application has already done. The System contains define cost structure template, input cost structure and simulate the student tuition fee. The system can help university to define their unit cost. The system has been tested using black box method is done at the level of departments, faculties, bureaus, and divisions in Sebelas Maret University.